2013
DOI: 10.1186/1471-2180-13-165
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the genes for HC-toxin biosynthesis in Alternaria jesenskae

Abstract: Background: HC-toxin, a cyclic tetrapeptide, is a virulence determinant for the plant pathogenic fungus Cochliobolus carbonum. It was recently discovered that another fungus, Alternaria jesenskae, also produces HC-toxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Another common feature of these gene clusters is the presence of a rather atypical bANK-type TF (ToxE and Aps2/Apf2) containing both a basic DNA-binding domain and four ankyrin repeats. ToxE/Aps2/Apf2-like TFs with reasonable amino acid identity and structure were recently also found in the genomes of Pyrenophora tritici-repentis , Setosophaeria turcica and Glomerella cingulata , and in all cases the TF-encoding genes are adjacent to four-module NRPS genes [61]. The DNA binding motifs for ToxE in C. carbonum (5′-ATCTCNCGNA-3′; [55]) and Apf2 in F. fujikuroi (5′-TGACGTGA-3′; this work) differ despite the high sequence similarity in the basic DNA binding and ankyrin domains of both TFs.…”
Section: Discussionmentioning
confidence: 90%
“…Another common feature of these gene clusters is the presence of a rather atypical bANK-type TF (ToxE and Aps2/Apf2) containing both a basic DNA-binding domain and four ankyrin repeats. ToxE/Aps2/Apf2-like TFs with reasonable amino acid identity and structure were recently also found in the genomes of Pyrenophora tritici-repentis , Setosophaeria turcica and Glomerella cingulata , and in all cases the TF-encoding genes are adjacent to four-module NRPS genes [61]. The DNA binding motifs for ToxE in C. carbonum (5′-ATCTCNCGNA-3′; [55]) and Apf2 in F. fujikuroi (5′-TGACGTGA-3′; this work) differ despite the high sequence similarity in the basic DNA binding and ankyrin domains of both TFs.…”
Section: Discussionmentioning
confidence: 90%
“…Most fungal species seem to be resistant to HDACi, though mechanisms of resistance have only rarely been reported , and some even make their own. Examples include the linear polyketide depudecin and the cyclic tetrapeptides HC‐toxin , and Trapoxin . Another fungal HDACi, apicidin (a cyclic tetrapeptide made by Fusarium spp.)…”
Section: Hdaci Are Natural Products That Can Kill or Manipulate Compementioning
confidence: 99%
“…A well-known example is the interspecific horizontal transfer of the ToxA effector gene from P. nodorum to Pyrenophora tritici-repentis , resulting in the emergence of the tan-spot disease on wheat ( Friesen et al, 2006 ). HGT of whole or partial SM gene clusters have also been proposed ( Patron et al, 2007 ; Slot and Rokas, 2011 ; Wight et al, 2013 ). In a more extreme example, horizontal transfer of whole supernumerary chromosomes containing HST biosynthetic gene clusters has been proposed to confer pathogenicity to different pathotypes of Alternaria alternata ( Akagi et al, 2009 ; Mehrabi et al, 2011 ).…”
Section: Genome Evolutionary Dynamics Of Sm Biosynthetic Genes In Funmentioning
confidence: 99%
“…Interspecific comparative genomic analysis identified HC-toxin gene cluster is present in another maize pathogen Setosphaeria turcica ( Condon et al, 2013 ). Interestingly, the HC-toxin gene cluster is also present in another plant-associated fungus, Alternaria jesenskae , which does not appear to be pathogenic to most plants ( Wight et al, 2013 ). Comparative phylogenomic analysis of NRPS genes among plant pathogens has also revealed that some NRPS genes have undergone recombination and modular rearrangement ( Bushley and Turgeon, 2010 ).…”
Section: Genome Evolutionary Dynamics Of Sm Biosynthetic Genes In Funmentioning
confidence: 99%